A study to evaluate the immediate effect of proprioceptive neuromuscular facilitation versus active dynamic stretching during warm-up on 20-meter sprint in amateur soccer players - Dsouza, Carol D.; Kumar, Neeraj (International Journal of Research in Medical Sciences, 2024)
Background: Soccer is a highly popular sport and is played worldwide. It is an explosive sport and has a high incidence of injuries. In soccer, sprinting dominates the majority of the game, and it imposes a demand on players to have strong, flexible, and dynamic lower limbs. Amateur soccer players don’t usually practice warm-ups before their matches; hence, an appropriate warm-up protocol is required that can be incorporated into the training routine of players to avoid injuries and improve performance. The current study aims to evaluate and compare the immediate effect of PNF stretching versus active dynamic stretching during warm-up on 20-meter sprint performance in amateur soccer players. Methods: According to the inclusion criteria, 80 amateur soccer players participated in this cross-sectional study design. They were randomly distributed into 2 groups: A) PNF stretching (N = 40) and B) active dynamic stretching (N = 40). Participants in both groups performed the 20-meter sprint test initially, followed by their respective warm-up intervention, after which the 20-meter sprint test was repeated and new readings were recorded. Results: Both Group A and Group B showed improved performance; however, Group B was significantly better. (p value<0.05). Conclusions: This study therefore concludes that both PNF and active dynamic stretching can be used as a warm-up protocol. However, according to the inter-group comparison, active dynamic stretching shows a noteworthy improvement in 20-m sprint performance in amateur soccer players.